m²-2m-4=0,则m³-m²-6m+2008=
3个回答
m²-2m=4
所以m³-m²-6m
=m³-2m²+m²-2m-4m
=m(m²-2m)+(m²-2m)-4m
=4m+4-4m
=4
所以原式=4+2008=2012
相关问题
(m+3m+5m+...+2009m)-(2m+4m+6m+...2008m)
(m+3m5m+7m+.2009m)-(2m+4m+6m.2008m)
(m+3m+5m+7m+.+2009m)-(2m-4m-6m-.-2008m)=?
若m^2-2m=1,则2m^2-4m+2008=______
合并同类项:(m+3m+5m+…+2009m)-(2m+4m+6m+…+2008m)
(教材变式题)若m是方程x 2 -2008x-1=0的根,则(m 2 -2008m+3)•(m 2 -2008m+4)的
已知(m-3)^2+|n+4|=0,求(m+n)^2008+(m+n)^2006+…+(m+n)^6+(m+n)^4+(
若m^2+m-1=0,则m^2009+m^2008+m^2007+……+m^2+m+2009的值为多少
若m2+m-1=0,则m3+2m2+2008的值为( )
m^2+4m+n^2-6n+13=0,则m+n=